Inequalities in Labour Market Consequences of Common Mental Disorders - Johan Jarl; Anna Linder; Hillevi Busch; Anja Nyberg; Ulf-G. Gerdtham (Lund University, School of Economics and Management, Department of Economics, 2018)
The burden of mental disorders continues to grow and is now a leading cause of disability worldwide. The prevalence of mental disorders is unequal between population subgroups, and these disorders are associated with unfavourable consequences in social and economic conditions, health and survival. However, how the negative effects of mental disorders are distributed among population subgroups is less studied. Our aim is to investigate how labour market consequences of Common Mental Disorders (CMD) differ over gender, age, education, and country of birth. We use a population sample from southern Sweden of patients diagnosed with CMD 2009-2012 and a matched general population control group with linked register information on employment, long-term sick leave, and disability pension. Logistic regression with interaction effects between CMD and sociodemographic indicators are used to estimate labour market consequences of CMD in the different population subgroups. CMD have a negative impact on all labour market outcomes studied, reducing employment while increasing the risk of long term sick leave and disability pension. However, the associated effect is found to be stronger for men than women, except for disability pension where consequences are similar. Surprisingly, high educated individuals suffer worse labour market consequences than low educated. Consequences of CMD in labour market outcomes are not consistent across different age-groups and country of birth. Inequalities in the labour market consequences of common mental disorders sometimes contributes to, and sometimes mitigates, societal inequalities in employment, long term sick leave and disability pension. When developing new strategies to tackle mental ill health in the population, it may therefore be motivated to consider not only inequalities in the prevalence of mental disorders, but also inequalities in the consequences of these disorders.
Keywords: I10; I14; J01; 330; Mental health; Inequality; Employment; Labour market